Kristus Menjelma dalam Algoritma: Kritik Kristologi Kontekstual di Fajar Artificial Intelligence - Frederick Ray Popo (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. The relationship between artificial intelligence (AI) and Christian theology is commonly exa-mined from moral and pastoral perspectives. This article adopts a dogmatic theological approach, focusing on the phenomenon of Jesus AI (Deus in machina). This literature-based study raises two key questions: (1) What model of Christology is emerging in the age of AI? (2) What dogma-tic objections can be raised against it? AI systems that assume the persona of Jesus have the potential to reshape Christian faith by systematically replicating the teachings of Christ. How-ever, there is a significant risk of reductionism when the identity of Jesus is reduced merely to that of a moral teacher. This leads to a form of “hybridized Christology” that blurs historical, theological, and technological boundaries. The study highlights the importance of dogmatic discernment in responding to these developments.Abstrak. Relasi antara artificial intelligence (AI) dan teologi Kristiani umumnya dikaji dari aspek moral dan pastoral. Artikel ini mengambil pendekatan teologi dogmatik, dengan fokus pada fenomena Jesus AI (Deus in machina). Studi pustaka ini mengajukan dua pertanyaan: (1) Model Kristologi apa yang terbentuk di era AI? (2) Keberatan dogmatis apa yang dapat diajukan terhadapnya? AI berwajah Yesus berpotensi membentuk ulang pemahaman iman Kristiani karena mampu mereplikasi ajaran Kristus secara sistematis. Namun, muncul risiko reduksionisme ketika iden-titas Yesus direduksi menjadi sekadar guru moral. Hal ini melahirkan “Kristologi campur sari” yang mengaburkan batas historis, teologis, dan teknologis. Kajian ini menekankan pentingnya kehati-hatian dogmatis dalam merespons perkembangan tersebut.